The Internalisation of Sociocultural and Thin-Ideal Standards in Sports Scale: Development and preliminary validation in female aesthetic sports athletes. Issue 2 (4th March 2018) - Scoffier-Mériaux, Stéphanie; Ferrand, Claude; d'Arripe-Longueville, Fabienne
Abstract : Thinness is a part of today's sociocultural standards of beauty and thus is implicated in body image dissatisfaction and eating disorders. In female aesthetic sports, thinness is a standard for aesthetics and performance. Measuring the internalisation of thin-ideal standards in these athletes may therefore help them to gain insight into the risks associated with body image dissatisfaction and disordered eating. This study aimed to develop and validate the Internalisation of Sociocultural and Thin-Ideal Standards in Sports (ISTISS) Scale. Four studies involving 357 female aesthetic athletes examined the exploratory factorial structure, temporal stability, and concurrent validity of the ISTISS, which gave rise to a 10-item scale with two subscales: internalisation of sociocultural standards and thin-ideal standards in sports. Internal consistencies were satisfactory and relationships with the self-regulation of eating attitude in sport were as expected. These findings provide preliminary evidence for the appropriateness of the ISTISS Scale for female aesthetic sports athletes.